Indigenous, biomedicine and faith healing ambiguity in Tanzania : Bridging the trio gaps through pastoral counselling - Ngugi, Eberhardt (Stellenbosch Theological Journal, 2022)
Treatment of diseases was known in Africa long before the coming of modern scientific medicine. The Africans had their own traditional folk healers who treated both organic and functional diseases. Knowledge of plants, soils and water with special properties have enabled them to deal with infections, bacteria, and diseases. Different kinds of plants, large and small, terrestrial, and lacustrine, constitute about 75% of traditional medicine. Animal products make up about 20%, and minerals constitute the remaining 5% (Alves and Rosa 2005:77). However, with the coming of missionaries some developments took place. Western medicine was introduced in dispensaries and hospitals with a natural explanation for all sickness and healing. Missionaries treated indigenous healing as superstition, and unworthy of belief by promoting biomedicine and faith healing through prayers. Hence, there is a need of bridging the trio gaps through pastoral counselling in order to make sustained efforts to foster collaboration among them.